Perbandingan Metode Ekstrapolasi Polinomial dan Ekstrapolasi Chebyshev pada Prediksi Total Ekspor Migas Tahun 2022 - Darussalam, M. Miftah; Vega, Marshanda Amalia; Octaria, Putri; Puspasari, Shinta (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
International trade plays a crucial role in strengthening relationships between nations, where production specialization and exports serve as strategies to address a country's production deficiencies. The focus on exports, particularly oil and gas exports in Indonesia, is key to economic growth. This study compares two primary extrapolation methods, namely polynomial and Chebyshev, to predict the volume of oil and gas exports in 2022. Actual data from 2019 to 2021 is utilized to evaluate the performance of these methods. The analysis results indicate that although both methods provide accurate predictions, polynomial extrapolation has a slightly lower error rate compared to Chebyshev. Using MAPE as the evaluation metric, polynomial extrapolation obtains a value of 28.48, while Chebyshev obtains 31.46. Furthermore, for the relative error, polynomial method yields 0.304466997 percent, and Chebyshev method yields 0.327263854. Therefore, the polynomial method is chosen as the preferred approach, predicting the total oil and gas exports to be 11,127.29.